Waste treatment and disposal - Harrison, Roy M., 1948-; Hester, R. E. (Royal Society of Chemistry, 1995)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. This Issue follows on from the review of waste incineration in Issue 2, providing a thorough and detailed review of other waste management options. Waste generation affects everyone, and its treatment and disposal are matters of increasing complexity and urgency. Waste Treatment and Disposal examines the environmental impact of sewage and industrial effluent treatment on inland and coastal waters, in the atmosphere and on land. It also looks into current practice in the design, engineering, operation and control of landfill sites, and the effect of changes in regulatory policy. A wide range of waste management practices result in atmospheric discharges and this book reviews the localized impacts and mitigation of the discharge and the regulatory framework within which waste management has to operate. Waste Treatment and Disposal also covers the general and technical issues facing the materials recycling industry; looks into the factors affecting deep underground storage of radioactive fuel waste produced by nuclear reactors; and provides data from a number of case studies in cost-benefit analysis, demonstrating the utility of a consistent economic theory of waste management.
Includes index.
Keywords: Factory and trade waste -- Environmental aspects -- Great Britain.; Refuse and refuse disposal -- Environmental aspects -- Great Britain.; Great Britain.; elektronické knihy; electronic books